Techno-Economic Energy Optimization of the Off-Grid Electrical System with Power to Gas Storage Technology - Huamán-Romaní, Yersi-Luis; García-Vilela, Lucy Mariella; Agreda Cerna, Henrry Wilfredo; Seminario-Morales, María-Verónica; Sánchez-Prieto, María-Gregoria; Gutiérrez-Gómez, Edgar; Silva, Giovanna Jackeline Serna; Carbajal, Nestor Cuba; Bedriñana, Marco Antonio Añaños; Cordero, Carmen-Rosa-Zenozain- (International Journal of Integrated Engineering, 2023)
Renewable energy sources (RESs) have undeniable advantages over the recent years not only to supply electrical demand but also electrical demand. However, maximum use of the RES’s power has always been challenging as high penetration of the RESs as well as their intermittent nature might compromise the distribution networks power flow constraints. This paper proposes optimal energy operation of the off-grid distribution network  (DN) with participation of the power-to-gas (PtG) storage system. In this regard, PtG system is considered as an energy supplier in the DN. The natural gas generated by using PtG is applied to backup diesel generators for meeting demand at peak times. The objective functions in the system are modeled based on technical and economic modeling including minimize the operation cost and maximize the system reliability. The optimal energy operation in the two case studies is assumed considering non-participation and participation of the PtG system. To solving of the energy optimization, particle swarm optimization algorithm is proposed. Finally, proposed case studies under numerical simulation are implemented for validation of the participation of the PtG system.